2020
DOI: 10.22159/ijpps.2020v12i4.36973
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Scopes, Methods and Rationale of Integrative Approach in Siddha Medicine With Biomedicine

Abstract: In India, according to WHO 2018 statistics, there were 63% of death occurred due to Non-communicable diseases (NCDs), in which Cardiovascular diseases were leading cause of death 27%, followed by Cancer 9%, Chronic respiratory disease 11%, Diabetes 3% and other NCDs 13%. This indicates that NCDs needs to become a priority in controlling and preventing. Therefore, the only effective intervention may be at controlling and preventing NCDs disease is Integrative Medicine. Integrative Medicine is a medical practice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Few cases affected from Osteo-arthritis were treated using Chuttigai therapy and documented 25 . The mechanism behind the hot metal cauterization and efficacy of Chuttigai therapy was already described [26][27][28] . Hence, it may be concluded that Siddha para-surgical therapy chuttigai (cauterization) is effective in treating small superficial pedunculated vascular lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Few cases affected from Osteo-arthritis were treated using Chuttigai therapy and documented 25 . The mechanism behind the hot metal cauterization and efficacy of Chuttigai therapy was already described [26][27][28] . Hence, it may be concluded that Siddha para-surgical therapy chuttigai (cauterization) is effective in treating small superficial pedunculated vascular lesions.…”
Section: Discussionmentioning
confidence: 99%
“…The multiplex PCR technique detects more than one pathogen in a single sample and is used to identify exons and sequences in spe-cific genes. However, the design of primers is difficult because they are meant to adhere to specific DNA sequences [3]. In nested-semi nested PCR, two sets of primers are utilized.…”
Section: Introductionmentioning
confidence: 99%
“…The first set of primer is an amplified sequence and the second set of primer is complementary to the first sequence which will be shorter than the first amplified product. This method is more specific but has disadvantages such as the 'primer and dimerization' cross reaction [3,4].…”
Section: Introductionmentioning
confidence: 99%